2016
DOI: 10.1063/1.4948666
|View full text |Cite
|
Sign up to set email alerts
|

The effect of millisecond flash lamp annealing on electrical and structural properties of ZnO:Al/Si structures

Abstract: The effect of millisecond flash lamp annealing (FLA) on aluminum doped ZnO (AZO) films and their interface with Si have been studied. The AZO films were deposited by magnetron sputtering on Si (100) substrates. The electrical and structural properties of the film and AZO/Si structures were characterized by current-voltage, capacitance-voltage, and deep level transient spectroscopy measurements, X-ray diffraction, and secondary ion mass spectrometry. The resistivity of the AZO film is reduced to a close to stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 50 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…The measured resistivity of the ZnO:Al films after FLA was in the range of 1.0×10 −3 Ω cm. Recently, Lindberg et al have shown that the resistivity of magnetron sputtered ZnO:Al on Si followed by FLA can be as low as 2×10 −4 Ω cm [202].…”
Section: Silicon Carbidementioning
confidence: 99%
“…The measured resistivity of the ZnO:Al films after FLA was in the range of 1.0×10 −3 Ω cm. Recently, Lindberg et al have shown that the resistivity of magnetron sputtered ZnO:Al on Si followed by FLA can be as low as 2×10 −4 Ω cm [202].…”
Section: Silicon Carbidementioning
confidence: 99%